Linguistic Analysis Of The Opposition Discourse In The Iraqi Parliament: An Analytical Study/ التحليل اللغوي لخطاب المعارضة في مجلس النواب العراقي: دراسة تحليلية - Marwa Hussein Ali; Iyad Nazim Jassim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study provides a comprehensive linguistic analysis of the political opposition discourse in the Iraqi Council of Representatives during the first parliamentary term (2006–2010). It employs textual discourse analysis to examine the linguistic features and rhetorical strategies used by opposition blocs to express their positions during parliamentary sessions, including withdrawal, boycott, and suspension of membership. The research highlights how these linguistic strategies reflect political and social conflicts within the parliamentary arena. The study draws on official session transcripts, statements by members of parliament, press releases, and media coverage, analyzing language at syntactic, semantic, and rhetorical levels, with a focus on tools such as negation, emphasis, metaphor, and simile. The time frame of the study covers 2006 to 2010, a critical period following the U.S. occupation, characterized by heightened political tensions and security challenges. Preliminary analysis indicates that the opposition used a variety of complex linguistic tools to express dissent, convey political pressure, and influence public opinion, while the political consensus of the period limited parliamentary oversight and weakened the opposition’s role, affecting legislative performance and democratic development. The study emphasizes the importance of language as a medium for understanding political processes and suggests that further research on subsequent parliamentary terms could enrich knowledge of Iraqi political discourse. Moreover, it contributes to understanding how such linguistic practices may benefit speakers of languages other than Arabic by providing insights into political communication and rhetoric in multilingual contexts.